BUS LISTRIK SEBAGAI ALTERNATIF MODA TRANSPORTASI UNTUK MENINGKATKAN KINERJA SIMPANG DAN BUNDARAN - Simanjuntak, Nurvita Insani Magdalena; Simanjuntak, Johan O; Saragih, Putra; Harianja, Jala; Silitonga, Rahmat; Sinaga, Marsel (Jurnal Teknik Sipil dan Arsitektur, 2026)
The phenomenon of congestion in urban areas has been inreasing rapidly over time. This is due to the growth in the number of vehicles not being matched by the growth in road capacity. Increasing road capacity can sometimes be a hindrance, causing other problems for commmunities livign nearby. Therefore, following the lead of other metropolitan cities to minimize congestion, Medan City launched a mass transportation system in 2024 aimed at reducing the use of private vehicles as the primary mode of travel for the public, called the Medan Electic Bus. For this reason, a study is needed to determine the level of congestion assessed based on the Degree of Saturation value of intersections and roundabouts in urban areas so that it can be known whether the presence of Electric Buses has been able to replace private vehicles as the main mode of transportation. The results of the analysis show that the Degree of Saturation value at several intersections is > 0,85; meaning that congestion conditions are still found both during morning and evening peak hours. This is also indicated by the value of the Electric Bus load factor obtained < 70%, meaning that the presence of Electric Buses is less desirable to replace private vehicles as the main mode of transportation. So it can be concluded that even though mass transportation has been provided, congestion conditions are still found at certain points in the urban area of Medan City.